2019
DOI: 10.1155/2019/9237459
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenism, Elevated 17-Hydroxyprogesterone and Its Urinary Metabolites in a Young Woman with Ovarian Steroid Cell Tumor, Not Otherwise Specified: Case Report and Review of the Literature

Abstract: We describe a case of a 24-year-old overweight woman who presented with hirsutism, secondary amenorrhea, clitoromegaly, and symptoms of diabetes mellitus (DM). While a diagnosis of polycystic ovary syndrome (PCOS) with its associated metabolic disturbances was initially considered, serum total testosterone, androstenedione, and 17-hydroxyprogesterone (17-OHP) measured by liquid chromatography tandem mass spectrometry (LC-MS/MS) were significantly increased. As 17-OHP did not increase upon ACTH (Synacthen) stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
(46 reference statements)
2
12
2
Order By: Relevance
“…Wong et al 6 recently reviewed 21 case reports of SCTs, NOS, with 17-OHP concentrations reported and found a prevalence of 81% of elevated 17-OHP, similar to our patient. Yılmaz-Ağladıoğlu et al 7 reported a 13-year-old female who experienced a 6 year delay in diagnosis of SCT, NOS, by ultrasound due to presumed CAH.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Wong et al 6 recently reviewed 21 case reports of SCTs, NOS, with 17-OHP concentrations reported and found a prevalence of 81% of elevated 17-OHP, similar to our patient. Yılmaz-Ağladıoğlu et al 7 reported a 13-year-old female who experienced a 6 year delay in diagnosis of SCT, NOS, by ultrasound due to presumed CAH.…”
Section: Discussionsupporting
confidence: 87%
“…SCTs NOS are of stromal cell origin with variable histological features. 6 The ovarian tumor from this case had abundant cytoplasm with fibrous bands of inflammation. Conversely, SCTs can also be classified as Leydig cell tumors with cytoplasmic crystals of Reinke, which the presented tumor lacked.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“… 5 , 6 More than half (56%–77%) of patients with an SCT-NOS show hyperandrogenic symptoms and signs of virilization, such as hirsutism, acne, deepened voice, clitoromegaly, amenorrhea, and infertility. 1 , 7 9 Additionally, it can present with estrogenic manifestations (6%–23%), such as menorrhagia or postmenopausal bleeding. Some patients also develop endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%